Proteome analysis identifies L1CAM/CD171 and DPP4/CD26 as novel markers of human skin mast cells. Issue 1 (25th May 2016) - Gschwandtner, M.; Paulitschke, V.; Mildner, M.; Brunner, P. M.; Hacker, S.; Eisenwort, G.; Sperr, W. R.; Valent, P.; Gerner, C.; Tschachler, E.
Abstract: Background: The function of skin mast cells has been well documented in IgE‐mediated allergic reactions, whereas other mast cell functions are poorly defined. This study aimed at identifying novel mast cell proteins by proteome analysis of primary human skin mast cells. Methods: The proteome of skin mast cells was compared to other cell types and analyzed using bioinformatics. The expression and function of two proteins hitherto not described in skin mast cells was investigated in isolated mast cells as well as in mast cells in situ . Results: Within the mast cell proteome, we identified 49 highly expressed proteins previously not described in mast cells; 21 of these proteins were found to be selectively expressed in mast cells. Two proteins, the neural cell adhesion molecule L1 and dipeptidyl peptidase 4, were further studied. L1 was found to be highly expressed in mast cells in normal, psoriasis, and mastocytosis skin. Dipeptidyl peptidase 4 was found to be expressed in mast cells in normal, psoriasis, and mastocytosis skin as well as in bone marrow mast cells in patients with systemic mastocytosis. In normal skin, mast cells were identified as a major source of dipeptidyl peptidase 4 and we also found that skin mast cells and fibroblasts secrete an active form of this enzyme. Conclusions: In a systematic proteomics approach we identified two novel mast cell proteins potentially relevant to skin homeostasis: neural cell adhesion molecule L1 and dipeptidyl peptidase 4.